Light‐Controlled Simultaneous "On Demand" Release of Cytotoxic Combinations for Bimodal Killing of Cancer Cells. Issue 30 (3rd May 2018) - Tessaro, André Luiz; Fraix, Aurore; Failla, Mariacristina; Cardile, Venera; Graziano, Adriana C. E.; Estevão, Bianca Martins; Rescifina, Antonio; Sortino, Salvatore
Abstract: In this contribution, we report a novel entirely photocontrolled nanoplatform comprising a binary mixture of pluronic copolymers capable of self‐assembling into core–shell micelles and co‐entrapping two photoactivatable components: a benzoporphyrin photosensitizer for photodynamic therapy (PDT) and coumarin‐photocaged chemotherapeutic agent Chlorambucil (CAB). The resulting supramolecular micellar assembly is about 30 nm in diameter with a polydispersity index <0.1, stable for more than 72 h, and exhibits excellent preservation of the photochemical properties of the two photoresponsive components, even though they are confined within the same host nanocarrier. Appropriate regulation of the relative concentrations of these components makes them capable of absorbing visible light in comparable amounts, leading to effective simultaneous photogeneration of singlet oxygen and photo‐triggered release of CAB. This "on demand" release of cytotoxic combinations results in amplified anticancer activity against MCF‐7 human breast adenocarcinoma cells. Abstract : Light‐controlled release : Pluronic copolymers capable of self‐assembling into core–shell micelles and co‐entrapping two photoactivatable components generate cytotoxic 1 O2 and Chlorambucil under the exclusive control of visible light, resulting in amplified mortality of cancer cell lines (see graphic).